PELAKSANAAN PEMUSNAHAN BARANG SITAAN NARKOTIKA (STUDI KEJAKSAAN NEGERI SERDANG BEDAGAI) - Parningotan, Richard Nayer; Eddy, Triono (JURNAL DOKTRIN REVIEW, 2023)
The large number of narcotics cases that have been successfully uncovered by law enforcers, until the narcotics traffickers have been convicted, means that it is the duty of law enforcers to then destroy the narcotics evidence that has been confirmed by the Court. Formulation of the problem of how to organize the destruction of confiscated narcotics goods, and the authority of the Prosecutor in carrying out the destruction of confiscated narcotics goods, as well as the obstacles faced by the Serdang Bedagai District Prosecutor's Office in destroying narcotics evidence. Empirical juridical research methods. The results of his research regarding the implementation of the destruction of confiscated narcotics goods are in Article 13 PP No. 40 of 2013, that confiscated goods are managed which includes confiscation, sealing, setting aside, testing, storing, securing, monitoring and destroying. The authority of the Prosecutor in carrying out the destruction of confiscated narcotics goods is permitted based on the Determination of the Head of the local District Prosecutor's Office, and based on the Court Decision. The Serdang Bedagai District Prosecutor's Office, in carrying out the destruction of narcotics evidence, was based on the Court Decision, but experienced internal obstacles, namely the location for destruction, the time limit for destruction, and the budget for destruction. related to external obstacles, namely the very high volume of narcotics cases, the absence of relevant institutions, so the suggestion is that it would be best if narcotics evidence could have been destroyed since the first instance court decision, so there is no need to wait for an final decision, and there should be special facilities provided for destruction. evidence of narcotics, so that possible adverse effects from destruction do not impact the environment and public health.